The Resonance of Debussy for United States Post-Modernists - Briscoe, James (Revue musicale OICRM, 2014)
This study draws upon interviews with It seeks to show that Claude Debussy continues to exert a presence in contemporary United States composition. It thus can be seen that Debussy already foresaw such a possibility when he wrote in 1908, “I am working on things that will be understood only by our grandchildren in the 20th children.” Composers interviewed were Leslie Bassett, William Bolcom, Dave Brubeck, Elliott Carter, John Corigliano, George Crumb, Richard Danielpour, Philip Glass, John Harbison, Tania León, Wynton Marsalis, Pauline Oliveros, Steve Reich, Bright Sheng, Joseph Schwantner, Steven Stucky, Robert Ward, and Ellen Taaffe Zwilich. Five resonances abide from Debussy: 1) that he has instigated multi-cultural listening including across national lines, 2) has contributed to a set of identifiable predispositions or mindsets (forming an “armature” for a composition), 3) has led to a changed attitude toward forming, 4) has superseded Schoenberg and Stravinsky in importance, and 5) has impressed U.S. composers by permitting any realm of possible but necessarily coherent choices.